Relationship between cardiac magnetic resonance derived extracellular volume fraction and myocardial strain in patients with non-ischemic dilated cardiomyopathy. (25th November 2020) - Azuma, M; Kato, S; Kodama, S; Hayakawa, K; Kagimoto, M; Iguchi, K; Fukuoka, M; Fukui, K; Iwasawa, T; Utsunomiya, D; Kimura, K; Tamura, K
Abstract: Background: The feature tracking (FT) technique has been proposed as a robust method to evaluate the myocardial strain using conventional cine magnetic resonance imaging (MRI) of the left ventricle. Data is limited regarding the relationship between FT-derived myocardial strain and diffuse myocardial fibrosis evaluated by T1 mapping in patients with non-ischemic dilated cardiomyopathy (NIDCM). Purpose: The aim of this study was to evaluate the correlation between extracellular volume (ECV) by T1 mapping and myocardial strain by FT in patients with NIDCM. Methods: A total of sixty-four patients with NIDCM (62±12 years) and 15 controls (62±11 years) were studied. Using a 1.5T MR scanner, pre- and post- T1 mapping images of LV wall at mid-ventricular level was acquired to calculate ECV by modified Look-Locker inversion recovery (MOLLI) sequence. Radial strain (RS), circumferential strain (CS) and longitudinal strain (LS) was assessed by FT technique. ECV and myocardial strain were compared using a 6-segment model at mid-ventricular level. Results: Compared to the controls, the NIDCM patients had a significantly higher ECV (0.30±0.02 vs. 0.24±0.01, p<0.001) and impaired myocardial strain (RS, 24.2±3.0 vs. 52.2±6.2, p<0.001; CS, −7.5±2.1 vs. −15.3±2.2, p<0.001; LS −10.4±3.5 vs. −20.2±4.7, p<0.001, respectively). Similar results were obtained when comparing all 6 myocardial segments (segment 7–12) (all p values <0.001). In a segment-based analysis, a significant positive correlation was found between the ECV and CS (r=0.26 to 0.41; all p values <0.05), a negative correlation was found between the ECV and RS (r=−0.31 to −0.41; all p values <0.05). In a patient-based analysis, there were significant positive correlations between the ECV and CS (r=0.45, p<0.001), ECV and LS from 2-chamber view (r=0.30, p=0.006), ECV and LS from 4-chamber view (r=0.37, p<0.001). There was a significant negative correlation between the ECV and RS (r=−0.43, p<0.001) (FIGURE) Conclusions: In NIDCM patients, severity of myocardial fibrosis evaluated by T1 mapping is associated with impaired myocardial strain by FT technique. Funding Acknowledgement: Type of funding source: None